Impact Study of the Hetauda-Dhalkewar-Inaruwa Transmission Line on the Operation of Integrated Nepal Power System - Ajay Shah; Sanjaya Neupane; Kamal Darlami (Advances in Engineering and Technology: An International Journal, 2023)
Despite Nepal’s abundant hydroelectric resources, a substantial disparity exists between its electricity supply and demand. This discrepancy is exacerbated by the absence of high-voltage transmission lines, hindering efficient power evacuation from a handful of generating plants. This not only incurs financial losses for the utility but also compromises the reliability of the power supply. A prime example is the protracted delay in the construction of the 576 KM long Hetauda-Dhalkebar-Inaruwa 400kV double-circuit Transmission Line, primarily due to challenges posed by local residents unwilling to relinquish their land.The Integrated Nepal Power System (INPS) heavily relies on power generation concentrated in the central mid-hills region. The construction of the Hetauda-Dhalkebar-Inaruwa (HDITL) 400kV double-circuit Transmission Line is crucial for routing power to industrialize these areas, potentially bolstering the national GDP and generating employment opportunities. Furthermore, it is essential to connect the current hydropower output of around 2300 MW to the INPS system via a high-voltage transmission line to maximize its utilization. The HDITL project not only reduces line losses but also enhances grid stability. It facilitates energy export and direct transmission of high-generation power, such as the 456 MW from Upper Tamakoshi, thus saving approximately 400 MW of power and preventing losses for both the Government of Nepal (GoN) and the Nepal Electricity Authority. This research not only calculates the reduction in power and energy losses with the commissioning of HDITL but also assesses its monetary benefits. Utilizing INPS data and Digsilent Power Factory 15.1 for power flow analysis, the study estimates that HDITL can prevent a power loss of about 26.276 MW. Furthermore, it demonstrates that HDITL significantly improves the total generation power factor in INPS, from 0.88 to 0.99, and enhances the voltage profile, underscoring its critical role in Nepal’s energy infrastructure development.